2012
DOI: 10.3171/2012.4.jns111916
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverters failing to occlude experimental bifurcation or curved sidewall aneurysms: an in vivo study in canines

Abstract: Flow diverters may succeed in treating straight sidewall aneurysms, but the same device repeatedly fails to occlude curved sidewall and end-wall bifurcation aneurysms. In vivo studies can be designed to test basic principles that, once validated, may serve to guide clinical use of new devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 24 publications
2
51
1
2
Order By: Relevance
“…We have previously tested both high-porosity braided selfexpanding stents and flow diverters in wide-neck, bifurcation, and giant aneurysm models, and failures have occurred, particularly when devices were deployed in a curved configuration. [1][2][3] Device deformations and subsequent heterogeneity in device porosity were frequent and sometimes quite substantial. [1][2][3] When in vivo porosities of the portion of the devices bridging the aneurysm ostium were measured, it became clear that these were strongly influenced by the discrepancy in diameter between the parent artery and the portion of the device that was free to expand at the level of the aneurysm neck.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously tested both high-porosity braided selfexpanding stents and flow diverters in wide-neck, bifurcation, and giant aneurysm models, and failures have occurred, particularly when devices were deployed in a curved configuration. [1][2][3] Device deformations and subsequent heterogeneity in device porosity were frequent and sometimes quite substantial. [1][2][3] When in vivo porosities of the portion of the devices bridging the aneurysm ostium were measured, it became clear that these were strongly influenced by the discrepancy in diameter between the parent artery and the portion of the device that was free to expand at the level of the aneurysm neck.…”
mentioning
confidence: 99%
“…We have previously shown in animal models that as these devices adapt to the constraints of local anatomy, the ensuing deformations can lead to substantial variations in device porosity between cases treated with the same device as well as wide variations in porosity along the different segments of the same device. 1,2 Ideally, the aim of a flow-diversion treatment strategy is to form a tubular conduit of optimal porosity that will normalize linear flow, reconstruct the parent vessel, and effectively occlude the aneurysm while preserving arterial branches and perforators. Because the amount of "metallic coverage" of aneurysm and branch ostia may affect treatment safety and efficacy, it is desirable to accurately predict when and to what extent these deformations will occur and how these will influence device porosity.…”
mentioning
confidence: 99%
“…The success of FD with sidewall aneurysms yet failing in bifurcation or giant fusiform aneurysms has been confirmed in animal models. [21][22][23] Early series and meta-analyses have suggested that FD is associated with good outcomes in proximal carotid aneurysms; results were not as good in fusiform or bifurcation aneurysms of the posterior circulation. 1,12,24,25 Perhaps most unsurprising, our survey confirms that anterior circulation and sidewall dispositions are aneurysm characteristics associated with frequent FD choices.…”
Section: Discussionmentioning
confidence: 99%
“…Focal zones of low porosity and residual flow specifically occur in curved segments or wide-neck aneurysms due to the deformation of the FD (8,13). This deformation at the TZ is a potential cause of failure of flow diversion in wide-neck curved and/or endwall aneurysms (2,(6)(7)(8)13). …”
Section: █ Discussionmentioning
confidence: 99%